USING LANGUAGE CASUAL STYLE IN TEENAGERS 17 YEARSOLD ON INSTAGRAM COMMENT - Indah Apriyani; Suwarsih Asmawati (IKIP Siliwangi, 2019)
This research paper aims to find out of casual style used by teenagers of social media instagram. Instagram comment is always used by teenagers to interact with their friends using casual style. This research used qualitative descriptive method. The object of this research is the casual style used on instagram comment by teenagers. The data are casual style words on instagram comment by teenagers used when interact with their friends. The data source is the post on their account on instagram and the researchers taken 9 post from 3 accounts that used on instagram comment and containing casual style that they were used. In analyzing the data, the researchers classifies the data into types of casual styles based on eggins theory.Based on analysis the researchers found that from 3 account and 9 post from their post the researchers conclude that there are 51 casual style that used on instagram comment by teenagers and there are 32 declarative types of casual style , there are 3 exclamative types of casual style, there is 7 introgative types of casual style and the last there are 11 harsh words type of casual style. The total of casual style that used on instagram comment by teenagers are 51 and there are 4 types of casual styles in that instagram comment. This means that the more appear of casual style are in declaratives.Keywords : Casual style, teenagers, instagram commen